2019
DOI: 10.4103/jcvjs.jcvjs_87_18
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and outcome after anterior cervical discectomy and fusion for degenerative cervical disc disease

Abstract: Background: Anterior cervical discectomy and fusion (ACDF) is a well-described surgical approach for symptomatic degenerative cervical disc disease which does not respond to conservative management. In the present study, we assessed clinical presentation and outcomes of ACDF. Materials and Methods: The present study was conducted from October 1, 2015, to October 31, 2017, in the Department of Neurosurgery, Narayana Medical College and Hospital, Nellore, Andhra Pradesh, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…In the present study, neck pain (28.6%) was the most common recurrent symptom after ACDF. This is consistent with Skrkhande’s 100 participants study, in which the most common recurrent symptoms were neck pain and bladder symptoms (39%) [ 10 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, neck pain (28.6%) was the most common recurrent symptom after ACDF. This is consistent with Skrkhande’s 100 participants study, in which the most common recurrent symptoms were neck pain and bladder symptoms (39%) [ 10 ].…”
Section: Discussionsupporting
confidence: 91%
“…Symptoms were significantly reduced after ACDF in this study. Srikhande et al found similar results, where most symptoms (neck pain, radicular pain, limb weakness, paresthesia, and limb stiffness) improved significantly after surgery [ 10 ]. Furthermore, a similar finding was reported in a study of 235 patients, which measured health-related quality-of-life outcomes, such as the visual analog scale (VAS) for neck pain and the neck disability index, and found that both were significantly reduced after ACDF [ 11 ].…”
Section: Discussionmentioning
confidence: 88%
“…We identified 12 prospective cohort studies[ 7 8 11 12 13 14 16 19 20 21 22 23 ] and 16 retrospective cohort studies. [ 6 9 10 15 24 25 26 27 28 29 30 31 32 33 34 35 ] Across all studies ( n = 4270), the rate of postoperative dysphagia at any point of time was 7.9%. Among prospective studies ( n = 1707), overall rates of postoperative dysphagia ranged from 0.5% to 34.5% with a pooled incidence of 11.1%.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum von Mises stresses in these three groups were 30. 23 Figure 6 shows the distributions of stresses in the C5 inferior endplates. Figure 7 shows the distributions of stresses in the traditional plate and new prosthesis groups.…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…However, the use of a titanium ACP may be associated with complications including dysphagia and soft tissue injury because of its large volume [6,14]. In addition, the high elastic modulus and rigid fixation of titanium ACP might result in graft stress shielding, leading to screws backing out and looseness of the titanium plate [23]. Thus, it is of great clinical significance to develop a new anterior cervical plate to solve these defects.…”
Section: Introductionmentioning
confidence: 99%